(untitled) (Journal of the College of Education for Women, 2020)
The current research is concerned with studying the decisive answers which are considered quick and conclusive. These answers can effectively interrupt the opponent’s argument and close the dialogue.This research is concentrated on deliberative methodology focusing on the decisive answer’s activity and ending them through several completing and argument sides. This research consists of an introduction and three parts, the current introduction is focused the light on the concept of decisive answers and its uses in literature and the scarce of speech, and how to consider it with one dialogue description,that dialogue constitute by ? The first part is concerned with those answers through the deliberative methodology and classifying decisive answers in sequence with those answers. Part two is dealt with arrangement and employment of arguments in decisive answers in consist with argument concept, it is studied the mechanism of presenting arguments in this field. The last and the third partis dealt with the origins and the essence of decisive answers through critical necessities that arguments are concentrated through.In this research, there is a concentration in dialogue necessities and the mechanism of intentions for the basis of those answers.